2018
DOI: 10.1302/2046-3758.72.bjr-2017-0217.r2
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following limb salvage after combat hindfoot injury are inferior to delayed amputation at five years

Abstract: ObjectivesThe surgical challenge with severe hindfoot injuries is one of technical feasibility, and whether the limb can be salvaged. There is an additional question of whether these injuries should be managed with limb salvage, or whether patients would achieve a greater quality of life with a transtibial amputation. This study aims to measure functional outcomes in military patients sustaining hindfoot fractures, and identify injury features associated with poor function.MethodsFollow-up was attempted in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…Improvements (and importantly, no deterioration) in mobility and pain status were demonstrated alongside unchanged levels of ‘none to minimal’ depression and anxiety and stable body mass index (27±3 kg·m 2 ). In light of the historical evidence,1 2 5 6 the outcomes demonstrated here are highly significant. Blair et al 20 found that return-to-duty rates were increased in servicemen who received an integrated orthotic and rehabilitation programme (51%) compared with an IDEO brace alone (13%).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Improvements (and importantly, no deterioration) in mobility and pain status were demonstrated alongside unchanged levels of ‘none to minimal’ depression and anxiety and stable body mass index (27±3 kg·m 2 ). In light of the historical evidence,1 2 5 6 the outcomes demonstrated here are highly significant. Blair et al 20 found that return-to-duty rates were increased in servicemen who received an integrated orthotic and rehabilitation programme (51%) compared with an IDEO brace alone (13%).…”
Section: Discussionmentioning
confidence: 83%
“…This is the first study to evaluate the medium-term (mean 34±11 months) effect of a PDAFO on functional and psychosocial outcomes in patients with foot and ankle trauma. The results suggest that the provision of a PDAFO to patients presenting with lower extremity injuries commonly considered to demonstrate poor long-term clinical outcomes1 6 7 has contributed to lasting favourable results in a range of patient-reported measures. Improvements (and importantly, no deterioration) in mobility and pain status were demonstrated alongside unchanged levels of ‘none to minimal’ depression and anxiety and stable body mass index (27±3 kg·m 2 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is recommended to locate the ends of the tendons or nerves sectioned and then fix them temporarily in the soft parts to avoid their retraction. Their repair will be secondarily performed once the wounded stabilized [34].…”
Section: Annals Of Reviews and Research D)mentioning
confidence: 99%
“…A lthough open extruded talus injuries are rare cases that have been described, a case of an open extruded talus and navicular has not yet been described to our knowledge [1][2][3][4][5] . We describe a case of this unique injury that was initially treated with debridement and primary closure without reimplanting the talus and navicular.…”
mentioning
confidence: 99%